PENERAPAN ASAS KEADILAN RESTORATIF TERHADAP PENYALAH GUNA NARKOTIKA DI KABUPATEN KARAWANG - Puti Priyana; Imanudin Affandi; Taun Taun (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2018)
The application of the principle of restorative justice against narcotics abuse in Karawang Regency is motivated by the regulation on medical and social rehabilitation in Articles 54 through Article 59, Article 103 and Article 127 paragraph (2) and paragraph (3) of Law Number 35 Year 2009 concerning Narcotics. The provision of rehabilitation of narcotics abuse according to the authors is one of the applications of the principle of restorative justice for abusers, especially narcotics. The author's research results at Karawang BNNK can be concluded that the application of the restorative principle of narcotics abuse based on Article 54-59, Article 103 and Article 127 paragraph (2) and paragraph (3) of Law Number 35 Year 2009 concerning Narcotics is only a concept only in a laws and regulations because it is considered a sanction that does not have a deterrent effect for abuse so it is feared that in addition to being an abuse, the offender has the potential to become a narcotics dealer later. Based on these conclusions, law enforcers must be consistent in applying the rule of law against narcotics abusers under what is regulated in Article 54-59, Article 103 and Article 127 paragraph (2) and paragraph (3) of Law Number 35 Year 2009 about Narcotics.